Pathways to healthy ageing in Vanuatu: a qualitative evaluation of national policy prioritiesResearch in context - Anna Palagyi; Thomas Gadsden; Jenny Stephens; Myriam Abel; Lindah Peter; Siwon Lee; Tsogzolmaa Bayandorj; Christopher Bates; Sébastien Libert (Elsevier, 2024)
Summary: Background: The Pacific Island country of Vanuatu is at the early stages of demographic ageing. The government is yet to develop a strategic approach to optimize the health and wellbeing of older indigenous Vanuatu residents (ni-Vanuatu). Methods: Using policy mapping and semi-structured interviews with 42 ni-Vanuatu, this research aimed to explore the current policy context surrounding ageing in Vanuatu and the priorities of older adults to inform preliminary steps to develop a national response to healthy ageing. Analyses were grounded in the World Health Organization's Regional Action Plan on Healthy Ageing in the Western Pacific. Findings: While the national policy context exhibited an indirect commitment to creating an environment conducive to healthy ageing, explicit policy commitments and monitoring indicators were lacking. Older persons reported numerous obstacles to healthy ageing, including financial insecurity, physical and psychological barriers to participation, and lack of community support. Interpretation: Findings highlighted the need for policymakers and stakeholders to focus preliminary strategic efforts on select components of the Regional Action Plan: evidence generation, advocacy/awareness, financing, community engagement and coordination, and family-centred empowerment. To ensure acceptability and sustainability, it is vital that these leverage existing strengths of traditional community values and the prevailing role of faith and religion in the lives of older ni-Vanuatu. Funding: This project was funded and supported by the World Health Organization (WHO) Regional Office for the Western Pacific (WPRO). Outcomes reflect the deliberations of authors and research partners.